A New Conveyable Device for Electro-drainage of Thorax - M Ghahramanifar; M Haghani; A Ghadimi Moghadam; A Haghani; A K Ghadimi (Journal of Biomedical Physics and Engineering, 2018)
Chest tube is a flexible plastic tube used to discharge secretion in the cavity between the lungs and chest named pleural cavity. Normally, there is a small amount of fluid in the cavity between the lungs and chest; This fluid helps the movement of lungs during breathing without abrasion. Entrance of bit of air, blood or pus because injury in the pleural cavity can prevent the lungs from fully opening. Full or partial collapse of the lungs makes breathing difficult and can lead to respiratory arrest; putting chest tube in the pleural cavity causes the discharge of secretion and helps patients comfort.